Lanthanum borate synthesis via the solid-state method from a La2O3 precursor: Electrical and optical properties - Sari, Selda; Senberber, Fatma Tugce; Yildirim, Meral; Kipcak, Azmi Seyhun; Yuksel, Sureyya Aydin; Derun, Emek Moroydor (ELSEVIER SCIENCE SA, 2017)
In this study, three different types of lanthanum borates, which have the structural formulas of La3BO6, LaBO3 and La(BO2)(3), were synthesized, such as diphasic and triphasic, by using the lanthanum source of La2O3 and boron sources of both H3BO3 and B2O3 via a solid-state route. The effects of reactant molar ratio, reaction temperature, time and atmosphere on the production of lanthanum borates were studied. X-ray diffraction (XRD), Fourier transform infrared (FTIR) and Raman Spectroscopy techniques were applied to the synthesized minerals for characterization, and the scanning electron microscopy (SEM) technique was used for the determination of surface morphologies and particle sizes. In addition, the optical and electrical characteristics of synthesized lanthanum borates with the highest XRD scores were investigated. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Electrical properties; Lanthanum borate; Optical properties; Solid-state; SINGLE-CRYSTALS; GROWTH; Materials Science